ВТОРАЯ КОММУНИКАЦИЯ (К ПОСТАНОВКЕ ВОПРОСА) (Филологические заметки, 2019)
Two types of communication are to be distinguished, two varieties of language functioning. The first one is the ordinary communication between the partners. In this case the process is directed from the speaker to the hearer, i.e. outside the speaker. The second one is presented by the “communication” of the speaker with himself – during reasoning. It is directed from the speaker to himself – inside the speaker. In the process of the first communication the partners talk about more or less familiar objects and events, using well known words, both simple and derivative. In the process of the second communication a man can discuss some new, unknown objects that have not yet any analogies with well known objects and so have no analogies with well known words. In such cases a man has “to invent” new words – to create new root-words which later can be followed by derivatives.
Keywords: first communication, second communication, derivation of words, invention of words